Caloric restriction mimetics: effects of spermidine and berberine on healthy longevity and prevention of aging-associated diseases. - Murillo Cancho, Antonio Fernando; Martín-Latorre, María del Mar; Lozano-Paniagua, David; Nievas-Soriano, Bruno José (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: Aging is a complex biological process associ ated with the accumulation of cellular damage, loss of pro teostasis, and mitochondrial dysfunction, which contribute to the development of chronic diseases. Spermidine and berberine are natural compounds with complementary properties that promote healthy longevity by targeting key cellular path ways such as autophagy and mitochondrial biogenesis. The objective of this review is to evaluate the mechanisms of action, benefits, and limitations of spermidine and berberine and to explore their synergistic potential as anti-aging agents in personalized medicine strategies. Methods: A narrative review of the scientific literature was conducted to analyze the effects of spermidine and berberine in preclinical and clinical models. Relevant studies focusing on molecular mechanisms, therapeutic applications, and practical limitations were examined. Results: Spermidine stimulates autophagy by inhibiting acetyltransferases, improving protein quality, and reducing toxic aggregates associated with cellular aging. Berberine activates AMPK and SIRT1, enhancing mitochondrial biogenesis and regulating energy metabolism. Both compounds have shown efficacy in animal models in improving cognitive function, reducing oxidative stress, and preventing metabolic diseases. However, their low bioavailability and the lack of longitudinal studies limit their clinical application. Discussion: The complementary effects of spermidine and berberine address proteostasis and cellular bioenergetics si multaneously. Their combination represents a promising multifactorial approach but requires advances in formulations to optimize absorption and stability. Clinical trials are essential to validate their safety and efficacy in humans. Conclusions: Spermidine and berberine have significant po tential as therapeutic agents in anti-aging medicine. Their in tegration into personalized therapies could improve quality of life and prevent chronic diseases, although additional studies are needed to overcome current limitations.